Mortalidade e avaliação dos serviços de atenção ao câncer de mama e ginecológico, Distrito Sanitário Oeste, Belo Horizonte, (1995) - Patricia Maria Fonseca Escalda (1998)
The objective of the work was to study the feminine mortality for both, breast and gynecological cancer, in the Distrito Sanitario Oeste DISAO (1995) and, secondanly, in the municipal district of Belo Horizonte (1981-1995), taking into consideration the organization, the availability and the access to the services of health that promote the prevention and the control of those diseases. The data sets used in this work came from two main sources of information. The first one provided the data originated from the statistics of the Civil Registration of the municipal district of Belo Horizonte and of DISAO, relative to the feminine deaths for breast and gynecological cancer. The population data sets used for calculation of estimates were provided by the Demographic Censuses of 1980, 1991 and 1996,supplied by the lBGE, the Brazilian Bureau of Census. The second one was constituted of primary data, collected from the application of specific questionnaires, especially elaborated for this work, answered by the professionals responsible for the gynecological clinics in the Centers of Health of DISAO. In order to evaluate the prevention actions and the control of the breast and cervix cancer, a qualitative methodology was used, through interviews with the medical professionals (gynecologists) and managers ofthe basic services of health of DISAO. Among the feminine deaths for cancer, in DISAO, the breast câncer represented the second main death cause and the utenrs câncer occupied the fifth position. The results demonstrated that, in Belo Horizonte, the mortality rate for breast cancer during the period 1981-1995 had increased from 20/100000 to 23/100000. For the same period, there was a slight increase on death rates for cervix cancer, from 7/100000 to 8/100000. The results showed here can contribute to the (re)organization of the project of the prevention actions and the control of the breast and gynecological cancer, that can be found in all services of health of the municipal district of Belo Horizonte. The expansion of the basic services of prevention of the main types of feminine reproductive cancer. through the incorporation of technologies, the systematic clinical exam and the educational process are simple tools capable to allow to women a longer lifetime.